CAFES 2009 new student survey report - Speerstra, Mandy; Trechter, David (My University, 2010)
During Academic Day, September 2, 2008, incoming freshmen and transfer students in the College of Agriculture, Food and Environmental Sciences (CAFES) were asked to complete a one-page questionnaire designed to find out: how they learned about UW-River Falls as an option for their tertiary education; what factors most influenced their decision to come here; what sorts of contact they had with the University prior to matriculating and how committed they feel to UW-River Falls and their current major. This is the third year in a row that the SRC has administered a survey to incoming students.
25 p.
Keywords: College of Agriculture, Food and Environmental Sciences; University of Wisconsin-River Falls. College of Agriculture, Food and Environmental Sciences; University of Wisconsin-River Falls--Students; College students--Wisconsin--River Falls